Efficacy of interventions with live combined Bacillus subtilis and Enterococcus faecium enteric-coated capsules in metabolic associated fatty liver disease patients: a meta-analysis of randomized controlled trials - Wu, Yutong; Wu, Hao; Yi, Hang (Frontiers in Pharmacology, 2025)
ObjectiveMetabolic associated fatty liver disease (MAFLD) is a common liver disease worldwide. However, effective therapies are still lacking. This meta-analysis aimed to compare the efficacy of interventions with or without live combined Bacillus subtilis and Enterococcus faecium (LCBE) enteric-coated capsules in MAFLD patients, thereby providing some reference for clinicians in optimizing treatment strategies.MethodsEmbase, PubMed, Web of Science, Cochrane Library, Wan Fang, China Science and Technology Journal Database, China National Knowledge Infrastructure, and China Biomedical Literature Service System were searched for relevant randomized controlled trials (RCTs). MAFLD patients receiving interventions with or without LCBE enteric-coated capsules were categorized into the experimental or control group, respectively.ResultsThis meta-analysis included 21 RCTs with 1783 MAFLD patients. The effective rate was higher in the experimental group than in the control group (P < 0.001). The normal and light fatty liver rate was increased in the experimental group compared to the control group (P = 0.003). Aspartate transaminase, alanine aminotransferase, and gamma-glutamyl transferase were lower in the experimental group than the control group (all P < 0.01). Body mass index, fasting blood glucose, triglyceride, total cholesterol, and low-density lipoprotein cholesterol were lower, and high-density lipoprotein cholesterol was higher in the experimental group than the control group (all P < 0.05). C-reactive protein, interleukin-6, tumor necrosis factor-alpha, and endotoxin were lower in the experimental group than in the control group (all P < 0.01).ConclusionInterventions containing LCBE enteric-coated capsules exhibit satisfactory efficacy, which improve liver function, metabolic status, and inflammation compared to those without LCBE enteric-coated capsules in MAFLD patients.